AliView: a fast and lightweight alignment viewer and editor for large datasets - Larsson, Anders (Bioinformatics (Oxford, England), 2014)
AliView is an alignment viewer and editor designed to meet the requirements of next-generation sequencing era phylogenetic datasets. AliView handles alignments of unlimited size in the formats most commonly used, i.e. FASTA, Phylip, Nexus, Clustal and MSF. The intuitive graphical interface makes it easy to inspect, sort, delete, merge and realign sequences as part of the manual filtering process of large datasets. AliView also works as an easy-to-use alignment editor for small as well as large datasets. Availability and implementation: AliView is released as open-source software under the GNU General Public License, version 3.0 (GPLv3), and is available at GitHub ( www.github.com/AliView ). The program is cross-platform and extensively tested on Linux, Mac OS X and Windows systems. Downloads and help are available at http://ormbunkar.se/aliview Contact:  anders.larsson@ebc.uu.se Supplementary information:  Supplementary data are available at Bioinformatics online.